Field notes contributed by Hank Zaletel, winter 1981-1982 - Zaletel, Hanket al (1981)
Field notes were contributed by Hank Zaletel. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1981-1982. Epson - sheet feed